2016
DOI: 10.1039/c6nr05584b
|View full text |Cite
|
Sign up to set email alerts
|

Lamellar MoSe2nanosheets embedded with MoO2nanoparticles: novel hybrid nanostructures promoted excellent performances for lithium ion batteries

Abstract: A carbon-free nanocomposite consisting of MoO nanoparticles embedded between MoSe nanosheets, named MoO@MoSe, has been synthesized and demonstrated excellent electrochemical properties for lithium ion batteries. In such a composite, MoSe nanosheets provide a flexible substrate for MoO nanoparticles; while MoO nanoparticles act as spacers to retain the desired active surface to electrolyte and also introduce metallic conduction. In addition, the heterojunctions at the interface between MoSe and MoO introduce a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
99
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(104 citation statements)
references
References 58 publications
5
99
0
Order By: Relevance
“…XPS is employed to measure the chemical states of Mo, Se, and O elements in MoSe 2 /MoO 2 . Mo 3d core‐level spectrum consists of four peaks at 232.3, 229.2, 228.6, and 231.7 eV (Figure c), which can be assigned to Mo 3d 3/2 and 3d 5/2 of MoO 2 and MoSe 2 , indicating the presence of MoO 2 and MoSe 2 after the selenization . The O 1s XPS peak (Figure d) at 530.4 eV corresponds to MoO 2 in Mo (IV) O bonds, which proves that MoO 2 have not been completely selenized.…”
Section: Resultsmentioning
confidence: 95%
“…XPS is employed to measure the chemical states of Mo, Se, and O elements in MoSe 2 /MoO 2 . Mo 3d core‐level spectrum consists of four peaks at 232.3, 229.2, 228.6, and 231.7 eV (Figure c), which can be assigned to Mo 3d 3/2 and 3d 5/2 of MoO 2 and MoSe 2 , indicating the presence of MoO 2 and MoSe 2 after the selenization . The O 1s XPS peak (Figure d) at 530.4 eV corresponds to MoO 2 in Mo (IV) O bonds, which proves that MoO 2 have not been completely selenized.…”
Section: Resultsmentioning
confidence: 95%
“…In the last few decades, by virtue of their high security, capability of storing clean energy, and providing a stable power supply, commercialized lithium‐ion batteries (LIBs) have come to dominate the energy storage market from portable electronic devices to electrical vehicles . However, limited Li sources and exorbitant prices have hampered their sustainable development . Therefore, sodium‐ion batteries (SIBs) and potassium‐ion batteries (PIBs), with analogical energy storage behavior to LIBs, have sparked significant attention and are considered as promising alternatives to LIBs, ascribed to their competitive cost, appropriate redox potential, along with inexhaustible sodium/potassium reserves, which can be more able to meet the urgent demands of large‐scale energy storage markets .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Fu and co‐workers reported that the vertical ReS 2 nanowalls on 3D graphene foam showed the first charge (Li + extraction) capacity of 640 mAh g −1 and maintained a capacity of 365 mAh g −1 after 100 cycles at a current density of 1 A g −1 . Cao and co‐workers reported that MoSe 2 nanosheets can provide a flexible substrate for MoO 2 nanoparticles, leading to a reversible capacity of 520.4 mAh g −1 at a current density of 2000 mA g −1 after 400 cycles …”
Section: Introductionmentioning
confidence: 99%